Tungsten-molybdenum-tantalum-niobium alloy powder material and preparation method thereof
By synthesizing tungsten disulfide nanotubes and adhesion of silicon carbide on the surface of tungsten-molybdenum tantalum niobium alloy powder and combining palm leaf cellulose reinforced filler, the low solubility and oxide particles problems during the alloying process are solved, and the machinery of the alloy is improved Performance and density.
Patent Information
- Application Number
- CN202411406877.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-10
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Tungsten powder, molybdenum powder, tantalum powder and niobium powder have problems with low solubility and incomplete reaction during the alloying process, which affects the uniformity and performance stability of the alloy. In addition, metal elements are prone to combine with oxygen to form oxide particles during the sintering process. , weaken the properties of alloy powder materials.
Tungsten disulfide nanotubes were synthesized on the surface of carbon fibers and mixed with silicon carbide and polyvinyl alcohol to form a gel, adhered to the surface of tungsten-molybdenum-tantalum niobium metal powder, used silicon carbide as a deoxidant to reduce oxygen content, and passed through palm leaves Cellulose coated nanosilicon dioxide as a reinforcement filler, filled in the gaps of the alloy powder to improve density.
The mechanical strength, tensile strength and yield strength of tungsten-molybdenum tantalum niobium alloy are improved, the uniformity and performance stability of the alloy are enhanced, the formation of oxide particles is avoided, and the sintering density and performance are improved.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite alloy material preparation, in particular to a tungsten-molybdenum-tantalum-niobium alloy powder material and a preparation method thereof. Background Art
[0002] Tungsten, molybdenum and their alloys are widely used in the power, aerospace, nuclear energy and materials sectors due to their high density, high temperature impact resistance and high strength, while tantalum, niobium and their alloys have low vapor pressure and excellent corrosion resistance. The high density of tungsten, the high rigidity of molybdenum, the high specific volume and biocompatibility of tantalum and niobium can be used as functional materials to assist in the fields of aerospace, new energy, and military. Refractory metals such as tungsten (W), molybdenum (Mo), tantalum (Ta), and niobium (Nb) are usually prepared by powder metallurgy to prepare tungsten-molybdenum-tantalum-niobium alloy powder, that is, by sintering the pressed raw materials at high temperature to obtain metal or alloy products, which have excellent properties such as high melting point, high hardness, high density, high strength, and corrosion resistance, and are widely used in various industries such as aerospace, chemical, and electronics.
[0003] Tungsten has poor sintering activity, low-temperature brittleness, and low mechanical properties. Therefore, the brittleness of tungsten can be reduced by introducing molybdenum, tantalum, and niobium atoms to partially replace tungsten atoms to form a tungsten-molybdenum-tantalum-niobium alloy. The formed alloy has a high melting point, hardness, density, mechanical strength, and corrosion resistance. However, there are large differences between tungsten powder, molybdenum powder, tantalum powder, and niobium powder. During the alloying process, problems such as low solubility and incomplete reaction will occur, affecting the uniformity and performance stability of the alloy. In addition, during the sintering process, metal elements are easily combined with oxygen to form oxide particles, which are enriched at the grain boundaries and weaken the performance of the alloy powder material. Summary of the invention
[0004] The invention aims to provide a tungsten-molybdenum-tantalum-niobium alloy powder material and a preparation method thereof: tungsten disulfide nanotubes are synthesized on the surface of carbon fibers, the cavity structure of the tungsten disulfide nanotubes is filled with carbon fibers, thereby avoiding the presence of pores in the alloy powder when the tungsten disulfide nanotubes are added, resulting in a decrease in the mechanical properties of the alloy; carbon fibers loaded with tungsten disulfide nanotubes, silicon carbide and polyvinyl alcohol are mixed to form a gel having good adhesion and can adhere to the surface of tungsten-molybdenum-tantalum-niobium metal powders, so that the tungsten-molybdenum-tantalum-niobium powders adhere to form a whole, and silicon carbide is used as a deoxidizer. During the sintering process, silicon carbide in the composite can first react with oxygen in the tungsten-molybdenum-tantalum-niobium mixture to reduce the oxygen content; palm leaf cellulose is coated on the surface of nano-silicon dioxide as a reinforcing filler. Due to the small size effect of nano-silicon dioxide, the reinforcing filler is filled in the gaps of the tungsten-molybdenum-tantalum-niobium metal powders, which is conducive to pressing into a dense preform, and during the sintering process, the palm leaf cellulose is thermally decomposed to generate a large amount of carbon elements that can react with metal elements in the tungsten-molybdenum-tantalum-niobium alloy to form metal carbides, thereby increasing the tensile strength and yield strength of the alloy.
[0005] The technical problem to be solved by the present invention is as follows: There are great differences among tungsten powder, molybdenum powder, tantalum powder and niobium powder. During the alloying process, problems such as low solubility and incomplete reaction will occur, which will affect the uniformity and performance stability of the alloy. In addition, during the sintering process, metal elements are easily combined with oxygen to form oxide particles, which are enriched at the grain boundaries and weaken the performance of the alloy powder material.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A tungsten-molybdenum-tantalum-niobium alloy powder material, comprising the following raw materials by weight: 55-60 parts of tungsten powder, 20-30 parts of molybdenum powder, 15-25 parts of tantalum powder, 5-10 parts of niobium powder, 1-3 parts of a composite material, and 0.2-0.4 parts of a reinforcing filler;
[0008] A method for preparing a tungsten-molybdenum-tantalum-niobium alloy powder material, specifically comprising the following steps:
[0009] Tungsten powder, molybdenum powder, tantalum powder, niobium powder, composite material and reinforcing filler are mixed and placed in a ball mill for ball milling for 1-3 hours to obtain a mixture, the mixture is placed in a pressure mold and pressed into a preform, and the preform is placed in a sintering furnace for high-temperature sintering, cooled to room temperature, and ground and polished to obtain a tungsten-molybdenum-tantalum-niobium alloy powder material.
[0010] Furthermore, the ball-to-material ratio in the ball mill is (1-3):(0.5-1.5).
[0011] Furthermore, the pressing pressure is 300-400 MPa, and the pressing time is 40-50 s.
[0012] Furthermore, the high temperature sintering temperature is 1700-2000°C, the high temperature sintering time is 2-5h, and the high temperature sintering vacuum pressure is 40-50Pa.
[0013] Furthermore, the composite is prepared by mixing carbon fiber loaded with tungsten disulfide nanotubes, silicon carbide and polyvinyl alcohol.
[0014] Furthermore, the tungsten disulfide nanotube has a diameter of 20-40 nm and a length of 2-3 μm.
[0015] Furthermore, the silicon carbide particle size is 30-60 nm, and the oxygen content is 0.1-0.2%.
[0016] Further, the composite is prepared by the following steps:
[0017] Citric acid and polyvinyl alcohol were added to deionized water and stirred evenly, and carbon fibers and silicon carbide loaded with tungsten disulfide nanotubes were added, and the mixture was stirred and reacted at 80° C. for 30 minutes to form a gel, which was filtered, washed with deionized water for 3 times, and dried in an oven at 60° C. for 10 minutes to obtain a composite.
[0018] Among them, citric acid and polyvinyl alcohol undergo a cross-linking reaction to form a gel-like substance, and the carboxyl and hydroxyl groups carried by the citric acid can combine with the hydroxyl groups on the surface of the carbon fiber and silicon carbide loaded with tungsten disulfide nanotubes, so that the carbon fiber and silicon carbide loaded with tungsten disulfide nanotubes are embedded in the gel, which has good adhesion and can adhere to the surface of tungsten, molybdenum, tantalum and niobium powders to form a whole.
[0019] Furthermore, the usage ratio of citric acid, polyvinyl alcohol, deionized water, carbon fiber loaded with tungsten disulfide nanotubes and silicon carbide is (10-11) g:(5-6) g:(45-55) mL:(1-2) g:(0.8-1.2 g).
[0020] Furthermore, the carbon fiber loaded with tungsten disulfide nanotubes is prepared by modifying the surface of the carbon fiber with dopamine, and then mixing the carbon fiber with ball-milled ammonium tetrathiotungstate and stirring the mixture for reaction.
[0021] Furthermore, the carbon fibers have a length of 3-5 μm and a diameter of 10-20 nm.
[0022] Furthermore, the carbon fiber loaded with tungsten disulfide nanotubes is prepared by the following steps:
[0023] A1. Add dopamine to a Tris-HCl buffer solution with a pH of 8.5, stir evenly, add carbon fiber, stir and react at 45°C for 2 hours, cool to room temperature, wash three times with deionized water, and dry in an oven at 70°C for 15 minutes to obtain pretreated carbon fiber.
[0024] Among them, in the Tris-HCl buffer solution, dopamine can react with carbon fiber, so that the carbon fiber has excellent adhesion, and can adhere the ball-milled ammonium tetrathiotungstate to the surface of the carbon fiber, which is beneficial to the synthesis of tungsten disulfide nanotubes on the surface of the carbon fiber.
[0025] Furthermore, the dosage ratio of dopamine, Tris-HCl buffer solution, and carbon fiber is (0.1-0.3) g: (80-120) mL: (0.3-0.7) g.
[0026] A2. Add the ball-milled ammonium tetrathiotungstate and pretreated carbon fiber into deionized water, stir for 30 minutes, filter, wash with deionized water, and dry in an oven at 60°C for 10 minutes to remove moisture to obtain a solid. Place the solid in a high-temperature reactor, introduce hydrogen and thiophene at a rate of 120 mL / min, heat to 400°C, and conduct a thermal reaction for 30 minutes. Pass the generated tail gas into tetrahydrofuran and 1 mol / L zinc sulfate solution, cool, and take out to obtain carbon fiber loaded with tungsten disulfide nanotubes.
[0027] The ball-milled ammonium tetrathiotungstate is adhered to the surface of the carbon fiber and placed in a high-temperature reactor. The catalyst hydrogen and thiophene are in contact with the ball-milled ammonium tetrathiotungstate on the surface of the carbon fiber, so that the atoms of the ball-milled ammonium tetrathiotungstate are arranged in a layered structure, and the edges of the ball-milled ammonium tetrathiotungstate layer are curled.
[0028] Furthermore, during the thermal reaction at 400°C, the ball-milled ammonium tetrathiotungstate is thermally decomposed to release ammonia and hydrogen sulfide gas. The layered structure of the ball-milled ammonium tetrathiotungstate forms a tubular structure just like a new leaf curling up after losing water, thereby forming tungsten disulfide nanotubes, thereby achieving tungsten disulfide nanotube coating on the surface of carbon fiber.
[0029] Furthermore, the amount ratio of the ball-milled ammonium tetrathiotungstate, pretreated carbon fiber, and deionized water is (3-5) g: (4-6) g: (45-55) mL.
[0030] Furthermore, the volume ratio of hydrogen to thiophene is (90-100):(4-6).
[0031] Further, the ball-milled ammonium tetrathiotungstate is prepared by the following steps:
[0032] The ammonium tetrathiotungstate is mixed with the stainless steel ball, sealed with a cover, vacuumed, introduced with argon, and ball-milled for 0.5-1.5h on a planetary ball mill at a pressure of 0.1-0.3MPa and a rotation speed of 450-550r / min to obtain ball-milled tungsten powder.
[0033] Furthermore, the mass ratio of ammonium tetrathiotungstate and stainless steel ball is (5-7):(20-30).
[0034] Furthermore, the diameter of the stainless steel ball is 5-7 mm.
[0035] Furthermore, the reinforcing filler is made by reacting a linker with palm leaf cellulose and then mixing it with nano-silica.
[0036] Furthermore, the linking agent is selected from 3-aminopropyltrimethoxysilane or γ-aminopropyltriethoxysilane.
[0037] Furthermore, the particle size of the nano-silicon dioxide is 20-30 nm.
[0038] Further, the reinforcing filler is specifically prepared by the following steps:
[0039] Add the linker to deionized water and ethanol, stir evenly, add nano-silica, stir evenly, stir and react at 70°C for 10 minutes, add palm leaf cellulose and 36% hydrochloric acid by mass, continue to react for 10 minutes, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 60°C for 10 minutes to obtain a reinforced filler.
[0040] Among them, the hydroxyl groups produced by the hydrolysis of the linker γ-aminopropyltriethoxysilane can react with the hydroxyl groups on the surface of nano-silica, and the amino groups of γ-aminopropyltriethoxysilane can be combined with the oxygen-containing functional groups of palm leaf cellulose through chemical bonds, so that the palm leaf cellulose is coated on the surface of nano-silica as a reinforcing filler. Due to the small size effect of nano-silica, the reinforcing filler is filled in the gaps of the alloy powder and dispersed in the alloy matrix.
[0041] Furthermore, the dosage ratio of the linker, deionized water, ethanol, nano-silicon dioxide, palm leaf cellulose, and hydrochloric acid is (1-3) g: (4-6) mL: (45-55) mL: (1-2) g: (5-6) g: (0.1-0.3) mL.
[0042] Furthermore, palm leaf cellulose is specifically prepared by the following steps:
[0043] The palm leaves were ground into powder, and the samples were washed with hot water at 60°C to remove dust and impurities on the surface. After drying, palm leaf powder was obtained. The palm leaf powder was placed in a 5% by mass sodium hydroxide aqueous solution, and stirred at 80°C for 2 hours to remove hemicellulose. The powder was taken out, washed, and dried, and placed in a 10% by mass hydrogen peroxide aqueous solution, and stirred at 80°C for 2 hours to degrade the lignin in the fiber. After filtering, the powder was washed with deionized water 3 times, and dried in an oven at 80°C for 8 minutes to obtain palm leaf cellulose.
[0044] Furthermore, the ratio of palm leaf powder, sodium hydroxide aqueous solution and hydrogen peroxide aqueous solution is (1-2):(20-30)mL:(15-25)mL.
[0045] Furthermore, compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) In the technical solution of the present invention, carbon fibers can prevent dislocation movement of tungsten-molybdenum-tantalum-niobium alloy and improve the strength of tungsten-molybdenum-tantalum-niobium alloy; tungsten disulfide nanotubes are synthesized on the surface of carbon fibers to form core-shell materials. Carbon fibers serve as the core material of tungsten disulfide nanotubes, so that the cavity structure of tungsten disulfide nanotubes is filled with carbon fibers, thereby avoiding the presence of pores in the alloy powder after tungsten disulfide nanotubes are added, which leads to a decrease in the mechanical properties of the alloy. On the other hand, the formed tungsten disulfide nanotubes are concentrated at the grain boundaries and defects of tungsten-molybdenum-tantalum-niobium alloy, which can refine the grains of tungsten-molybdenum-tantalum-niobium alloy and improve the mechanical strength of the alloy. The thermal expansion mismatch between the two materials, tungsten disulfide nanotubes and the alloy interface, increases the dislocation density of the alloy, thereby hindering the development of cracks under load. In addition, the formed carbon fibers loaded with tungsten disulfide nanotubes have an excellent aspect ratio and are dispersed in the alloy matrix, which can absorb stress and reduce the brittleness of tungsten.
[0047] (2) In the technical solution of the present invention, carbon fiber loaded with tungsten disulfide nanotubes, silicon carbide and polyvinyl alcohol are mixed, and citric acid is used as a cross-linking agent. The formed gel has good adhesion and can adhere to the surface of tungsten, molybdenum, tantalum and niobium metal powders, so that the tungsten, molybdenum, tantalum and niobium powders adhere to form a whole; wherein, silicon carbide is used as a deoxidizer. During the sintering process, silicon carbide in the composite can react before oxygen in the tungsten, molybdenum, tantalum and niobium mixture, reduce the oxygen content, and avoid the presence of oxygen in the tungsten, molybdenum, tantalum and niobium mixture causing tungsten to be brittle. In addition, silicon carbide in the composite filler reacts with oxygen to generate amorphous silicon dioxide, thereby purifying the tungsten grain boundaries and improving the sintering density and strength of the material. In addition, the formation of amorphous silicon dioxide reduces the sintering activation energy of the tungsten, molybdenum, tantalum and niobium alloy, accelerates the sintering rate, can reduce energy consumption, and can avoid long-term sintering resulting in the tungsten, molybdenum, tantalum and niobium alloy material having excessively coarse grain size and disordered microstructure, which affects the performance of the alloy powder material.
[0048] (3) In the technical solution of the present invention, during the sintering process, silicon carbide can also react with the tungsten element in the nanotubes on the surface of the carbon fiber loaded with tungsten disulfide nanotubes to form tungsten carbide as a reinforcing phase, thereby improving the performance of the tungsten-molybdenum-tantalum-niobium alloy, and the carbon fiber is tightly bonded to the tungsten-molybdenum-tantalum-niobium alloy through the formed tungsten carbide.
[0049] (4) In the technical solution of the present invention, palm leaf cellulose is coated on the surface of nano-silicon dioxide as a reinforcing filler. Due to the small size effect of nano-silicon dioxide, the reinforcing filler is filled in the gaps of the tungsten, molybdenum, tantalum and niobium metal powders, which is conducive to pressing into a dense preform. Palm leaf cellulose contains a large amount of carbon elements. During the sintering process of the tungsten, molybdenum, tantalum and niobium metal powders, the palm leaf cellulose is thermally decomposed to produce a large amount of carbon elements that can react with the metal elements in the tungsten, molybdenum, tantalum and niobium alloy to form a small amount of metal carbides with a diameter of about 70-100nm that are approximately spherical or ellipsoidal. It exists in the grain boundaries and grains of tungsten-molybdenum-tantalum-niobium alloy, and as the strengthening phase of the alloy, it produces a composite strengthening effect of solid solution strengthening and dispersion strengthening, increases the tensile strength and yield strength of the alloy, and the tungsten powder, molybdenum powder, tantalum powder and niobium powder are connected by carbides, which improves the uniformity and performance stability of the alloy; in addition, the nano-silicon dioxide released by the thermal decomposition of palm leaf cellulose fills the tiny cracks of the tungsten-molybdenum-tantalum-niobium alloy when it is prone to slip under the action of external force, thereby improving the strength and density of the tungsten-molybdenum-tantalum-niobium alloy. It contains silicon, which can reduce the defects of pores in aluminum alloy. DETAILED DESCRIPTION
[0050] The technical solutions in the embodiments of the present invention are described clearly and completely. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0051] The raw materials used in the embodiments of the present invention are as follows:
[0052] Tungsten powder: particle size is 4-5μm, purity is 99.5%, oxygen content is 0.25%.
[0053] Molybdenum powder: particle size is 1.2-2μm, purity is 99.9%.
[0054] Tantalum powder: particle size is 10-11μm, purity is 99.9%.
[0055] Niobium powder: particle size is 2.3-2.6μm, purity is 99%.
[0056] The silicon carbide particle size is 30-60nm and the oxygen content is 0.1-0.2%.
[0057] Carbon fiber: 3-5μm in length and 10-20nm in diameter.
[0058] The ball-milled ammonium tetrathiotungstate is prepared by the following steps:
[0059] Mix 6 g of ammonium tetrathiotungstate and 25 g of stainless steel balls (with a diameter of 5-7 mm), seal with a lid, evacuate, introduce argon, and mill on a planetary ball mill at a pressure of 0.2 MPa and a rotation speed of 500 r / min for 1 h to obtain ball-milled tungsten powder.
[0060] Example 1
[0061] The composite is specifically prepared by the following steps:
[0062] A1. Add 0.2 g dopamine to 100 mL Tris-HCl buffer solution with a pH of 8.5, stir evenly, add 0.5 g carbon fiber, stir and react at 45°C for 2 h, cool to room temperature, wash 3 times with deionized water, and dry in an oven at 70°C for 15 min to obtain pretreated carbon fiber.
[0063] A2. Add 4 g of ball-milled ammonium tetrathiotungstate and 5 g of pretreated carbon fiber into 50 mL of deionized water, stir for 30 min, filter, wash with deionized water, and dry in an oven at 60 ° C for 10 min to remove moisture to obtain a solid. Place the solid in a high-temperature reactor, introduce hydrogen and thiophene at a rate of 120 mL / min, heat to 400 ° C, and conduct a thermal reaction for 30 min. The generated tail gas is introduced into tetrahydrofuran and 1 mol / L zinc sulfate solution, cooled, and taken out to obtain carbon fiber loaded with tungsten disulfide nanotubes.
[0064] A3. Add 10.5 g of citric acid and 5.6 g of polyvinyl alcohol to 50 mL of deionized water, stir evenly, add 1.5 g of carbon fiber loaded with tungsten disulfide nanotubes and 1 g of silicon carbide, stir and react at 80°C for 30 min to form a gel, filter, wash with deionized water 3 times, and dry in an oven at 60°C for 10 min to obtain a composite.
[0065] Comparative Example 1
[0066] The difference between this comparative example and Example 1 is that no pretreated carbon fiber is added, and the remaining steps and raw materials are the same as Example 1.
[0067] A1. Place 4g of ball-milled ammonium tetrathiotungstate in a high-temperature reactor, introduce hydrogen and thiophene at a rate of 120mL / min, heat to 400°C, and conduct thermal reaction for 30min. The generated tail gas is introduced into tetrahydrofuran and 1mol / L zinc sulfate solution, cooled, and taken out to obtain carbon fiber loaded with tungsten disulfide nanotubes.
[0068] A2. Add 10.5 g of citric acid and 5.6 g of polyvinyl alcohol to 50 mL of deionized water, stir evenly, add carbon fiber and silicon carbide loaded with tungsten disulfide nanotubes, stir and react at 80°C for 30 min to form a gel, filter, wash with deionized water 3 times, and dry in an oven at 60°C for 10 min to obtain a composite.
[0069] Comparative Example 2
[0070] The difference between this comparative example and Example 1 is that silicon carbide, citric acid and polyvinyl alcohol are not added, and the remaining steps and raw materials are the same as Example 1.
[0071] A1. Add 0.2 g dopamine to 100 mL Tris-HCl buffer solution with a pH of 8.5, stir evenly, add 0.5 g carbon fiber, stir and react at 45°C for 2 h, cool to room temperature, wash 3 times with deionized water, and dry in an oven at 70°C for 15 min to obtain pretreated carbon fiber.
[0072] A2. Add 4 g of ball-milled ammonium tetrathiotungstate and 5 g of pretreated carbon fiber to 50 mL of deionized water, stir for 30 min, filter, wash with deionized water, and dry in an oven at 60°C for 10 min to remove moisture to obtain a solid. Place the solid in a high-temperature reactor, introduce hydrogen and thiophene at a rate of 120 mL / min, raise the temperature to 400°C, and conduct a thermal reaction for 30 min. The generated tail gas is introduced into tetrahydrofuran and 1 mol / L zinc sulfate solution, cooled, and taken out to obtain a composite.
[0073] Example 2
[0074] The reinforcing filler is specifically prepared by the following steps:
[0075] B1. Grind palm leaves into powder, wash the sample with hot water at 60°C to remove dust and impurities on the surface, and obtain palm leaf powder after drying. Place 1.5g of palm leaf powder in 25mL of 5% sodium hydroxide aqueous solution, stir at 80°C for 2h to remove hemicellulose, take out, wash and dry, place in 20mL of 10% hydrogen peroxide aqueous solution, stir at 80°C for 2h to degrade lignin in the fiber, filter, wash with deionized water 3 times, and dry in an oven at 80°C for 8min to obtain palm leaf cellulose.
[0076] B2. Add 2g of γ-aminopropyltriethoxysilane to 5mL of deionized water and 50mL of ethanol, stir evenly, add 1.5g of nano-silicon dioxide, stir evenly, stir and react at 70°C for 10min, add 5.5g of palm leaf cellulose and 0.2mL of 36% hydrochloric acid, continue to react for 10min, cool to room temperature, filter, wash with deionized water 3 times, and dry in an oven at 60°C for 10min to obtain a reinforced filler.
[0077] Comparative Example 3
[0078] The difference between this comparative example and Example 2 is that palm leaf cellulose is not added, and the remaining steps and raw materials are the same as Example 2.
[0079] Comparative Example 4
[0080] The difference between this comparative example and Example 2 is that no nano silicon dioxide is added, and the remaining steps and raw materials are the same as Example 2.
[0081] Example 3
[0082] A tungsten-molybdenum-tantalum-niobium alloy powder material, comprising the following raw materials by weight: 55 parts of tungsten powder, 20 parts of molybdenum powder, 15 parts of tantalum powder, 5 parts of niobium powder, 1 part of a composite material, and 0.2 parts of a reinforcing filler;
[0083] A method for preparing a tungsten-molybdenum-tantalum-niobium alloy powder material, specifically comprising the following steps:
[0084] Tungsten powder, molybdenum powder, tantalum powder, niobium powder, composite material and reinforcing filler are mixed and placed in a ball mill for ball milling for 1-3 hours to obtain a mixture, the mixture is placed in a pressure mold and pressed into a preform, and the preform is placed in a sintering furnace for high-temperature sintering, cooled to room temperature, and after grinding and polishing, a tungsten-molybdenum-tantalum-niobium alloy powder material is obtained, wherein the ball-to-material ratio in the ball mill is 2:1, the pressing pressure is 350MPa, the pressing time is 45s, the high-temperature sintering temperature is 1880℃, the high-temperature sintering time is 3h, and the high-temperature sintering vacuum pressure is 45Pa.
[0085] The tungsten-molybdenum-tantalum-niobium alloy powder material contains 54.1% tungsten, 21.8% molybdenum, 16.6% tantalum, 5.2% niobium, 0.8% carbon, 0.6% silicon, 0.3% sulfur, and the remainder is unavoidable impurities.
[0086] Example 4
[0087] A tungsten-molybdenum-tantalum-niobium alloy powder material, comprising the following raw materials by weight: 58 parts of tungsten powder, 25 parts of molybdenum powder, 20 parts of tantalum powder, 8 parts of niobium powder, 2 parts of compound, and 0.3 parts of reinforcing filler;
[0088] A method for preparing a tungsten-molybdenum-tantalum-niobium alloy powder material, specifically comprising the following steps:
[0089] Tungsten powder, molybdenum powder, tantalum powder, niobium powder, composite material and reinforcing filler are mixed and placed in a ball mill for ball milling for 1-3 hours to obtain a mixture, the mixture is placed in a pressure mold and pressed into a preform, and the preform is placed in a sintering furnace for high-temperature sintering, cooled to room temperature, and after grinding and polishing, a tungsten-molybdenum-tantalum-niobium alloy powder material is obtained, wherein the ball-to-material ratio in the ball mill is 2:1, the pressing pressure is 350MPa, the pressing time is 45s, the high-temperature sintering temperature is 1880℃, the high-temperature sintering time is 3h, and the high-temperature sintering vacuum pressure is 45Pa.
[0090] The tungsten-molybdenum-tantalum-niobium alloy powder material contains 55.6% tungsten, 22.2% molybdenum, 17.1% tantalum, 5.5% niobium, 0.9% carbon, 0.65% silicon, 0.35% sulfur, and the remainder is unavoidable impurities.
[0091] Example 5
[0092] A tungsten-molybdenum-tantalum-niobium alloy powder material, comprising the following raw materials by weight: 60 parts of tungsten powder, 30 parts of molybdenum powder, 25 parts of tantalum powder, 10 parts of niobium powder, 3 parts of composite material, and 0.4 parts of reinforcing filler;
[0093] A method for preparing a tungsten-molybdenum-tantalum-niobium alloy powder material, specifically comprising the following steps:
[0094] Tungsten powder, molybdenum powder, tantalum powder, niobium powder, composite material and reinforcing filler are mixed and placed in a ball mill for ball milling for 1-3 hours to obtain a mixture, the mixture is placed in a pressure mold and pressed into a preform, and the preform is placed in a sintering furnace for high-temperature sintering, cooled to room temperature, and after grinding and polishing, a tungsten-molybdenum-tantalum-niobium alloy powder material is obtained, wherein the ball-to-material ratio in the ball mill is 2:1, the pressing pressure is 350MPa, the pressing time is 45s, the high-temperature sintering temperature is 1880℃, the high-temperature sintering time is 3h, and the high-temperature sintering vacuum pressure is 45Pa.
[0095] The tungsten-molybdenum-tantalum-niobium alloy powder material contains 56.2% tungsten, 22.4% molybdenum, 17.4% tantalum, 5.9% niobium, 1% carbon, 0.7% silicon, 0.4% sulfur, and the remainder is unavoidable impurities.
[0096] Comparative Example 5
[0097] The difference between this comparative example and Example 4 is that the composite is replaced by the substance prepared in Comparative Example 1, and the remaining steps and raw materials are the same as those in Example 4.
[0098] Comparative Example 6
[0099] The difference between this comparative example and Example 4 is that the composite is replaced by the substance prepared in Comparative Example 2, and the remaining steps and raw materials are the same as those in Example 4.
[0100] Comparative Example 7
[0101] The difference between this comparative example and Example 4 is that the reinforcing filler is replaced by the material prepared in Comparative Example 3, and the remaining steps and raw materials are the same as Example 4.
[0102] Comparative Example 8
[0103] The difference between this comparative example and Example 4 is that the reinforcing filler is replaced by the material prepared in Comparative Example 4, and the remaining steps and raw materials are the same as those in Example 4.
[0104] The performance of the tungsten-molybdenum-tantalum-niobium alloy powder materials prepared in Examples 3-5 and Comparative Examples 5-8 is now tested;
[0105] Tensile strength test: The width and thickness of the sintered sample of the tungsten-molybdenum-tantalum-niobium alloy powder material prepared above were measured with a vernier caliper, and the average value was taken after three measurements. The tensile strength test was carried out on an Instron-3369 tensile testing machine at a tensile speed of 2 mm / min.
[0106] Microhardness test: The prepared tungsten-molybdenum-tantalum-niobium alloy powder material is placed on a HXD-1000T Vickers hardness tester to measure the surface hardness of the sintered sample. A load of 0.2 kg is applied to make the outline of the diamond indentation clearly visible. The indenter is pressed into the surface of the tested sample under the action of the applied load. After maintaining the pressure for a certain period of time, the load is removed and the hardness data is recorded by reading the value displayed on the screen.
[0107] Density performance test: The tungsten-molybdenum-tantalum-niobium alloy powder material prepared above is placed on a CP214 electronic balance for measurement. The mass in the air is m0; the tungsten-molybdenum-tantalum-niobium alloy powder is immersed in water, and the test mass is m0. p0 is the density of the liquid medium. The actual density of the alloy powder is p1 = (m0·p0) / (m0-m0). The same method is used to test the theoretical density p2 of the sample, and its density = p1 / p2.
[0108] Yield strength: Male C57BL / 6J mice were intravenously injected with 0.1 mL of the microorganism inhibitory composition. Blood samples were collected at 3 h, 6 h and 24 h after injection, plasma samples were harvested by centrifugation, and the blood concentration of the microorganism inhibitory composition was quantitatively detected using a fluorescence spectrophotometer.
[0109] The results are shown in Table 1 below:
[0110] Table 1
[0111] project Tensile strength / MPa Microhardness / HV Density / % Yield Strength Example 3 587 787 94.5 482 Example 4 595 800 95.6 496 Example 5 592 795 95.2 493 Comparative Example 5 537 753 93.1 433 Comparative Example 6 542 761 86.7 441 Comparative Example 7 527 746 92.1 421 Comparative Example 8 558 773 87.9 452
[0112] It can be seen from the data in Table 1 that the mechanical properties of the composite prepared by adding no pretreated carbon fiber to Comparative Example 5, which is used to prepare tungsten-molybdenum-tantalum-niobium alloy powder material, are reduced. This may be because the carbon fiber is used as the core material of the tungsten disulfide nanotube, so that the cavity structure of the tungsten disulfide nanotube is filled with the carbon fiber, thereby avoiding the presence of pores in the alloy powder when the tungsten disulfide nanotube is added, resulting in a reduction in the mechanical properties of the alloy; the mechanical properties and density of the composite prepared by adding no silicon carbide, citric acid and polyvinyl alcohol to Comparative Example 6 are reduced. This may be because the gel formed by citric acid and polyvinyl alcohol has good adhesion and can adhere to the surface of the tungsten-molybdenum-tantalum-niobium metal powder to form a whole, and silicon carbide is used as a deoxidizer. During the sintering process, silicon carbide in the composite can be mixed with tungsten, molybdenum, tantalum and niobium before tungsten. The oxygen in the material reacts to reduce the oxygen content, avoiding the brittleness of tungsten caused by the presence of oxygen in the tungsten-molybdenum-tantalum-niobium mixture; in comparative example 7, the reinforcing filler prepared without adding palm leaf cellulose was used to prepare the tungsten-molybdenum-tantalum-niobium alloy powder material, and its mechanical properties were reduced. This may be because the palm leaf cellulose contains a large amount of carbon elements that react with the metal elements in the tungsten-molybdenum-tantalum-niobium alloy to form metal carbides, which exist at the grain boundaries and in the grains of the tungsten-molybdenum-tantalum-niobium alloy, and serve as a strengthening phase of the alloy to increase the tensile strength and yield strength of the alloy; in comparative example 8, the reinforcing filler prepared without adding nano-silicon dioxide was used to prepare the tungsten-molybdenum-tantalum-niobium alloy powder material, and its mechanical properties and density were reduced. This may be because the nano-silicon dioxide fills in the tiny cracks of the tungsten-molybdenum-tantalum-niobium alloy when it is prone to slip under the action of external force, thereby improving the strength and density of the tungsten-molybdenum-tantalum-niobium alloy.
[0113] The data in Table 1 show that the tungsten-molybdenum-tantalum-niobium alloy powder materials prepared in Examples 3-5 meet the test performance requirements, while the tungsten-molybdenum-tantalum-niobium alloy powder materials prepared in Comparative Examples 5-8 do not meet the performance requirements, indicating that the tungsten-molybdenum-tantalum-niobium alloy powder materials prepared in the present invention have good mechanical properties and density.
[0114] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0115] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A tungsten-molybdenum-tantalum-niobium alloy powder material, characterized in that: The raw materials include: 55-60 parts of tungsten powder, 20-30 parts of molybdenum powder, 15-25 parts of tantalum powder, 5-10 parts of niobium powder, 1-3 parts of compound, and 0.2-0.4 parts of reinforcing filler; The composite is prepared by mixing carbon fiber loaded with tungsten disulfide nanotubes, silicon carbide and polyvinyl alcohol; The carbon fiber loaded with tungsten disulfide nanotubes is prepared by modifying the surface of carbon fiber with dopamine, and then mixing with ball-milled ammonium tetrathiotungstate and stirring for reaction; The reinforcing filler is prepared by mixed reaction of a connector, palm leaf fiber and nano silicon dioxide.
2. The tungsten-molybdenum-tantalum-niobium alloy powder material according to claim 1, characterized in that: The carbon fiber has a length of 3-5 μm and a diameter of 10-20 nm; the tungsten disulfide nanotube has a diameter of 20-40 nm and a length of 2-3 μm.
3. The tungsten-molybdenum-tantalum-niobium alloy powder material according to claim 1, characterized in that: The ball-milled ammonium tetrathiotungstate is prepared by the following steps: The ammonium tetrathiotungstate is mixed with the stainless steel ball, sealed with a cover, vacuumed, introduced with argon, and ball-milled for 0.5-1.5h on a planetary ball mill at a pressure of 0.1-0.3MPa and a rotation speed of 450-550r / min to obtain ball-milled tungsten powder.
4. The tungsten-molybdenum-tantalum-niobium alloy powder material according to claim 3, characterized in that: The mass ratio of the ammonium tetrathiotungstate and the stainless steel ball is (5-7):(20-30); the diameter of the stainless steel ball is 5-7 mm.
5. The tungsten-molybdenum-tantalum-niobium alloy powder material according to claim 1, characterized in that: The silicon carbide has a particle size of 30-60 nm and an oxygen content of 0.1-0.2%.
6. The tungsten-molybdenum-tantalum-niobium alloy powder material according to claim 1, characterized in that: The linking agent is selected from 3-aminopropyltrimethoxysilane or γ-aminopropyltriethoxysilane.
7. The tungsten-molybdenum-tantalum-niobium alloy powder material according to claim 1, characterized in that: The palm leaf cellulose is specifically prepared by the following steps: The palm leaves are ground into powder, and the sample is washed with 50-70° C. deionized water, and dried to obtain palm leaf powder. The palm leaf powder is placed in a 5% by mass sodium hydroxide aqueous solution, stirred, taken out, washed, dried, placed in a 10% by mass hydrogen peroxide aqueous solution, stirred, filtered, washed, and dried to obtain palm leaf cellulose.
8. The tungsten-molybdenum-tantalum-niobium alloy powder material according to claim 7, characterized in that: The dosage ratio of the palm leaf powder, the sodium hydroxide aqueous solution and the hydrogen peroxide aqueous solution is (1-2): (20-30) mL: (15-25) mL.
9. A method for preparing a tungsten-molybdenum-tantalum-niobium alloy powder material according to any one of claims 1 to 8, characterized in that: The following steps are involved: Tungsten powder, molybdenum powder, tantalum powder, niobium powder, composite material and reinforcing filler are mixed and placed in a ball mill for ball milling for 1-3 hours to obtain a mixture, the mixture is placed in a pressure mold and pressed into a preform, and the preform is placed in a sintering furnace for high-temperature sintering, cooled to room temperature, and ground and polished to obtain a tungsten-molybdenum-tantalum-niobium alloy powder material.
10. The tungsten-molybdenum-tantalum-niobium alloy powder material according to claim 9, characterized in that: The ball-to-material ratio in the ball mill is (1-3):(0.5-1.5); the pressing pressure is 300-400MPa, and the pressing time is 40-50s; the high-temperature sintering temperature is 1700-2000°C, the high-temperature sintering time is 2-5h, and the high-temperature sintering vacuum pressure is 40-50Pa.